Metronidazole and 2-Methylimidazole as Corrosion Inhibitors in Microbiologically Influenced Corrosion (Journal of Scientific Research, 2022)
Microbial corrosion behavior of mild steel was studied by exposing mild steel coupons in Barr’s medium inoculated with sulfate-reducing bacteria (Desulfovibrio desulphuricans). During the investigation, a considerable loss in weight and deterioration of microstructure of mild steel coupons surface was observed. Coupons were further exposed to culture media containing different concentrations of metronidazole (MNZ) and 2- methylimidazole (MIZ) inhibitors. The corrosion behavior of mild steel was measured by weight loss, electrochemical studies, and SEM. Polarization studies indicated the mixed-type behavior of these inhibitors. MNZ and MIZ exhibited 82.23 and 78.30 % inhibition efficiencies, respectively, as revealed by polarization measurements. The results show that the inhibition efficiencies increased with inhibitor concentration. The surface analysis was performed by scanning electron microscopy (SEM).